Rancang Bangun “SI-BEGAL TRANSPORTASI” SEBAGAI Inovasi Media Pembelajaran Berbasis Scanning Untuk Praremaja - Bintari, Akmal; Purbasari, Brilian Triyuda; Mukti, Suci Sekar; Anindita, Reza Yoga (FSTPT Indonesia, 2024)
Providing monotonous learning material makes teenagers get bored quickly in class. Learning while playing is considered more effective in explaining material presented to adolescents. As a learning media, it introduces the world of transportation with quantitative and qualitative methods. This is aimed at teenagers to understand more about driving safety, traffic signs, road markings, and pedestrian procedures.